Pelatihan Microsoft Word sebagai Upaya Meningkatkan Kompetensi Dasar Siswa SMP Ahmad Yani 3 Tambakrejo - Kharisma Sinta Darmayanti (Nawasena Bhakti, 2025)
The rapid advancement of information technology demands early mastery of digital skills, including proficiency in word processing applications such as Microsoft Word. However, students at SMP Ahmad Yani 3 Tambakrejo still face limitations in using Microsoft Word to support their learning activities. This activity aimed to improve students’ basic competencies in operating Microsoft Word through hands-on training. The implementation method consisted of three stages: presentation of basic material, practical demonstrations, and assignment of individual tasks. The training involved around 40 students from grades 7 and 8. The results showed a significant improvement in students' ability to use basic Microsoft Word features, such as typing, text formatting, inserting images and tables, and saving documents properly. Beyond technical skills, the training also enhanced students’ confidence in using technology. In conclusion, the training proved effective in addressing students' basic technological needs and had a positive impact on the learning process. It is recommended that similar programs be continued and expanded to include other Microsoft Office applications to further enrich students' digital competencies in a sustainable manner.